Synergistic antitumor activity of regorafenib and rosuvastatin in colorectal cancer - Tao Yuan; Ruilin Wu; Weihua Wang; Yue Liu; Wencheng Kong; Bo Yang; Qiaojun He; Qiaojun He; Qiaojun He; Hong Zhu; Hong Zhu; Hong Zhu (Frontiers Media S.A., 2023)
Introduction: Colorectal cancer is one of the most prevalent life-threatening malignant tumors with high incidence and mortality. However, the efficacy of current therapeutic regimens is very limited. Regorafenib has been approved for second- or third-line treatment of patients who are refractory to standard chemotherapy diagnosed with metastatic colorectal cancer, but its clinical efficacy needs to be further improved. Accumulating evidence demonstrates that statins also possess potent anticancer activities. However, whether regorafenib and statins pose synergistic anticancer effects in colorectal cancer is still unclear.Methods: Sulforhodamine B (SRB) assays were applied to evaluate the anti-proliferative activity of regorafenib or/and rosuvastatin in vitro, and immunoblotting analysis were applied to detect the effects of regorafenib/rosuvastatin combined treatment on mitogen-activated protein kinase (MAPK) signaling and apoptosis-related proteins. MC38 tumors were applied to investigate the synergistic anticancer effects of regorafenib in combination with rosuvastatin in vivo.Results: We found that regorafenib in combination with rosuvastatin exerted significant synergistic inhibition against colorectal cancer growth in vitro and in vivo. Mechanistically, regorafenib and rosuvastatin combination synergistically suppressed MAPK signaling, a crucial signaling pathway promoting cell survival, as indicated by the reduction of phosphorylated MEK/ERK. In addition, regorafenib in combination with rosuvastatin synergistically induced the apoptosis of colorectal cancer in vitro and in vivo.Discussion: Our study demonstrated the synergistic anti-proliferative and pro-apoptotic effects of regorafenib/rosuvastatin combined treatment in colorectal cancer in vitro/vivo and might potentially be evaluated as a novel combination regimen for clinical treatment of colorectal cancer.